STRATEGI PENGEMBANGAN KLUSTER INDUSTRI LEDRE PISANG DI KABUPATEN BOJONEGORO - Sudirman Sudirman; Dodyk Pranowo; Wike Agustin Prima Dania (AGROINTEK, 2021)
Ledre is one of the signature snacks from Bojonegoro Regency. The center for producing bananas ledre in Bojonegoro Regency are in Padangan and Purwosari Districts. The main ingredient used in producing ledre is plantain which grown in Bojonegoro Regency. The banana ledre industry has various problems such as the capital, labor, product quality, marketing and there is no cluster division for each type of business. The purpose of this study was to determine the cluster and strategy for the development of banana ledre industry in Bojonegoro Regency. The method used was K-means Clustering and Fuzzy Analytical Hierarchy Process (FAHP). The results of the analysis were determined as many as 3 clusters, they were cluster 1 as the medium industry group, cluster 2 for small industry group and cluster 3 for the household industry group. The alternative strategy for cluster 1 development is to collaborate with the Bojonegoro Regency Office to provide training and education for workers and the establishment of SOPs for workers. The alternative strategy for cluster 2 development is to collaborate with financial institutions in Bojonegoro Regency with competitive interest rates and establish cooperation with the Office of Cooperatives and SMEs related to the venture capital. While the alternative strategy for developing cluster 3 is cooperation with the Bojonegoro District Office regarding legality licensing and improving the quality of packaging materials.